Analysis of the antenna settings, overlapping zones, interferences and data throughput in order to improve the quality of the Vodafone LTE mobile network by optimising the electrical tilts of the antennas. (2016)
This dissertation sets out to improve the quality of the Vodafone LTE network in the south-Germany by examining and correcting diferent parameters of antennas within a cluster and optimising their electrical tilts. It also aims to strengthen the student's knowledge, acquired during the telecommunications engineering bachelor at Santo Thomas University Colombia. The cellular network business has become more competitive and complex since the introduction of 4G. LTE has surpassed its predecessors, dominating data services and it is only matter of time before it fully extends to voice services, until we reach a point where the days of planning GSM, GPRS, WCDMA and UMTS are behind us. Human behaviour on social networks and the internet requires the best of network capacity now, which is why engineers must keep optimising processes constantly.